The Islamization of the Golden Horde: New Data » - Il’nur Mirgaleev (Золотоордынское обозрение, 2016)
The author of this article points out that although the Golden Horde was created as the result of conquests that terminated the existence of such Muslim states as the Khwarazmian Empire and Volga Bulgaria, nevertheless Muslims perceived the territory of the Golden Horde as “Dar al-Islam”, that is the “territory of Muslims”. In the author’s view, the reasons for this lie in the fact that Jochi himself and Batu were in close contact with the Baghdad Caliphate, whence the first Sufi missionaries came, who together with the Central Asian missionaries engaged in spreading Islam among the population of the Golden Horde, and especially among the Tatar elite. Particularly successful in this were Qalandars, Sufis from Anatolia. Islamization took place not only among the sedentary and, first of all, urban population, but the similar transformations happened also among nomadic population of the Golden Horde. Even during the reign of non-Muslim rulers in the Golden Horde, who came to power after khan Berke, the process of Islamization was not interrupted. The author believes that Sufis had been active from the first days of the Golden Horde, and they documented their vision of the Golden Horde history. In the author’s opinion, the history outlined in original Turkic-Tatar sources, for example written by Ötemish Hajji and Abdulgaffar Kyrymi, transmit exactly this “Islamized” history of the Jochids. When the story concerns Muslim khans, such as Berke and Uzbek, it accentuates the role of sheikhs. Data from the theological work the “Qalandar-name”, created in the Golden Horde, provides much new factual material on the issue of spread of Islam. The Qalandars were very knowledgeable about Islam and they were practicing Sufis who devoted themselves to proselytizing Islam. They distinguished themselves from other missionaries through their appeal, first of all, to the rulers. Therefore, their activities were clandestine and secret. The author connects their appearance in the Golden Horde with khan Berke’s activities, because he married to a Seljuk princess and rescued the last Seljuk princes from Byzantine captivity. According to the “Islamized” history of the Golden Horde, khans Berke and Uzbek as well as Janibek were pious Muslim rulers, who possessed all the best Muslim qualities, and absolutely the most important, they also participated in spreading of Islam as disciples of one or another sheikh. It is known that, for example, khans Janibek and Berdibek were raised by atalyks, that is by Sufi mentors. The history of the first Golden Horde khans draws parallels with the history of Islam during its early centuries, where khan Berke resembles the companion of the prophet Abu Bakr, and khan Janibek the companion of Omar.